Identifikasi dan Pemetaan Aspek Internal Berdampak Sistemik Terhadap Kinerja Pegawai Industri Perbankan di Indonesia Menggunakan Fuzzy Delphi dan Fuzzy Dematel - Sigit Kristiyanto; Jovi Sulistiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Employee performance is a fundamental pillar of sustainability and competitiveness in the banking industry. However, empirical studies are still largely dominated by partial and linear approaches that view performance as the outcome of isolated individual variables. In fact, within the complex and highly regulated banking organizational context, employee performance represents a systemic output shaped by dynamic interactions among internal organizational aspects. This study aims to identify and map internal aspects that systemically influence employee performance in the Indonesian banking industry, as well as to determine strategic aspects that function as key driving, linkage, and dependent factors within the causal structure of performance. This research adopts an exploratory approach by integrating the Fuzzy Delphi Method and Fuzzy DEMATEL. The Fuzzy Delphi Method is employed to validate performance aspects and criteria based on expert consensus involving banking practitioners, regulators, and academics. Subsequently, Fuzzy DEMATEL is applied to map causal relationships and influence structures among the relevant aspects and criteria. The Fuzzy Delphi results indicate that, out of six initial internal aspects and 31 criteria, only four aspects and ten criteria demonstrate structural relevance to the employee performance system, namely internal economic aspects, work culture, managerial aspects, and socio-psychological aspects. Meanwhile, individual and work environment aspects are eliminated due to the lack of expert consensus. The Fuzzy DEMATEL analysis reveals that economic and managerial aspects act as the main driving factors, while socio-psychological aspects function as linkage factors that mediate structural influences on employee performance. Work culture is positioned as a dependent factor, indicating that it is the most affected aspect within the system.. These findings emphasize that improving employee performance in the banking sector is ineffective when pursued through purely individual-level interventions. Instead, performance enhancement should focus on strengthening internal aspects with high systemic leverage. This study contributes conceptually by modeling employee performance as a systemic phenomenon and practically by providing a basis for prioritizing managerial policies and interventions grounded in the identified causal structure.